Evaluacion de la aplicación de agua ozonificada a dos dosis en Pitahaya. - Samaniego Izurieta, Christian Paul (2022)
In this research project, ozone was applied at different concentrations 0.3 ppm and 0.5 ppm on pitahaya as a pre- and post-harvest treatment, with the objective of knowing the incidence of ozone on pitahaya in relation to its persistence. For which pitahayas of approximately 200 plants were collected randomly in El Edén, Tres Juanes parish belonging to the Palora canton; These pitahayas presented three important characteristics in relation to the degree of maturity, that is, first, third and sixth grade. Regarding the use of ozone, it was carried out in the following way: in pre-harvest, fumigation was carried out using a backpack pump one day before harvest in the previously selected plants. later, in the postharvest, the ozone was placed once the fruit was harvested. The measurement of the parameter in postharvest was developed under environmental parameters in the facilities of the Microbiology Laboratory of the Technical University of Cotopaxi. The trial consisted of 18 treatments, of which 6 were used as controls. The control was carried out by mind and the following physical-chemical parameters were measured for 21 days: pH, total soluble solids, humidity, weight and firmness.